Youm AlHashir in Holy Quran: Surat Alansan as A Case Study - Ali Howair Swailem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Surah Al-Insan has a great place, as it is one of the surahs that included clarification of many aspects of a person’s life, how he was created, his fate on the Day of Resurrection, and determining his location, whether he is in Paradise or Hell. The Surah included the Day of Judgment and described it with three characteristics (gloomy frowning, widespread evil, and a heavy day, The surah explained the conditions of the people of Hell in two verses that include the existence of a painful torment for them through chains, shackles, blazing fire, and painful torment. Surat Al-Insan detailed the conditions of the people of Paradise and that they are in great bliss and dominion.